Tebrophen — An Old Polyphenol Drug with Anticancer Potential (†) - Rubelj, Ivica (Molecules, 2012)
In vitro high-throughput screening was carried out in order to detect new activities for old drugs and to select compounds for the drug development process comprising new indications. Tebrophen, a known antiviral drug, was found to inhibit activities on inflammation and cancer related targets. In primary screening this semisynthetic halogenated polyphenol was identified to inhibit the activities of kinases ZAP-70 and Lck (IC(50) 0.34 µM and 16 µM, respectively), as well as hydrolase DPPIV (at 80 µM 41% inhibition). Next, it showed no cytotoxic effects on standard cell lines within 24 h. However, tebrophen slowed propagation of breast cancer (MDA-MB-231), osteosarcoma (U2OS) and cervical carcinoma (HeLa), through at least 35 population doublings in a dose-dependent manner. It completely stopped the division of the prostate cancer (PC3) cell line at 50 µM concentration and the cells entered massive cell death in less than 20 days. On the other hand, tebrophen did not influence the growth of normal fibroblasts. According to the measured oxidative burst and estimated in silico parameters its direct antioxidative ability is limited. The obtained results indicate that tebrophen can be considered a promising lead molecule for generating more soluble derivatives with specific anticancer efficacy.